2022
DOI: 10.1523/jneurosci.2045-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Expectations Shape Cortical Reinstatement of Sensory Representations

Abstract: When making a turn at a familiar intersection, we know what items and landmarks will come into view. These perceptual expectations, or predictions, come from our knowledge of the context, however it's unclear how memory and perceptual systems interact to support the prediction and reactivation of sensory details in cortex. To address this, human participants learned the spatial layout of animals positioned in a cross maze. During fMRI, participants of both sexes navigated between animals to reach a target, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 65 publications
1
18
1
Order By: Relevance
“…We also hypothesised that this representation would be reflected in the subiculum as it travelled from the hippocampus to the cortex [7,8]. Previous research has found a change in the com-plexity of representations along the long axis of the hippocampus [24], and that the posterior hippocampus is involved in signalling perceptual predictions and prediction errors based on simple associations [8,9,25]. Therefore, we predicted that the posterior hippocampus and its subfields would contain information about the expected shape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also hypothesised that this representation would be reflected in the subiculum as it travelled from the hippocampus to the cortex [7,8]. Previous research has found a change in the com-plexity of representations along the long axis of the hippocampus [24], and that the posterior hippocampus is involved in signalling perceptual predictions and prediction errors based on simple associations [8,9,25]. Therefore, we predicted that the posterior hippocampus and its subfields would contain information about the expected shape.…”
Section: Resultsmentioning
confidence: 99%
“…The hippocampus has recently been suggested as an essential region coordinating learning and exploitation of predictive relationships for perceptual inference [3,4]. Representations of predicted stimuli have been found in the hippocampus [57], and informational connectivity between the hippocampus and visual cortex increases after an association has been learnt [8,9]. However, with typical fMRI analyses, these studies could not determine whether the hippocampus was re-sponsible for passing these predictions to the cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not explicitly address this question, we suspect that the hallucinations observed here are task-induced, in that they may be brought upon by strong expectations about encountering visual motion immediately after the cue at the start of each trial 40 . In fact, several recent reports have proposed that hippocampal neural representations generate cued predictions about upcoming sensory events, modulating activity in sensory cortex in a predominantly top-down fashion [41][42][43][44] .…”
Section: Hallucinatory Motion In the Riddoch Syndrome Correlates With...mentioning
confidence: 99%
“…Previous fMRI studies have identified history-dependent representations in the brain during context-dependent sequence learning tasks (Clarke et al, 2022; Hsieh et al, 2014) but these studies have not sought to discriminate between the three possibilities listed above. The first goal of our study is to test for all three types of history-dependent representation during context-dependent sequence learning.…”
Section: Introductionmentioning
confidence: 99%